2016
DOI: 10.14739/2310-1237.2016.1.71577
|View full text |Cite
|
Sign up to set email alerts
|

Changes of general cerebral symptoms in patients with traumatic brain injury and their dependence on the -675 4G/5G polymorphism in the plasminogen activator inhibitor-1 gene

Abstract: Зміни загальномозкової симптоматики у хворих із черепно-мозковою травмою залежно від -675 4G/5G поліморфізму гена інгібітора активатора плазміногена 1 типу Сумський державний університет, медичний інститут, м. Суми Ключові слова: черепно-мозкова травма, -675 4G/5G поліморфізм генетичний, плазміногена активатора інгібітор 1, неврологічні прояви.Черепно-мозкова травма (ЧМТ) посідає перше місце за показниками летальності та інвалідизації людей працездатного віку. Всесвітня організація охорони здоров'я щорічно фік… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous evidence has demonstrated that alternative treatment procedures combining drainage and intraventricular fibrinolysis with recombinant tissue plasminogen activator may prevent haemorrhagic complications (25). Notably, a previous study has reported the changes of focal and brainstem neurological signs in patients with traumatic brain injury and their dependence on the -675 4/5 G polymorphism in the PAI-1 gene (26). Therefore, in the present study it was assumed that plasma PAI-1 level may be associated with the degree of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has demonstrated that alternative treatment procedures combining drainage and intraventricular fibrinolysis with recombinant tissue plasminogen activator may prevent haemorrhagic complications (25). Notably, a previous study has reported the changes of focal and brainstem neurological signs in patients with traumatic brain injury and their dependence on the -675 4/5 G polymorphism in the PAI-1 gene (26). Therefore, in the present study it was assumed that plasma PAI-1 level may be associated with the degree of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%